The Relationship between Caring Burden and Quality of Life in Caregivers of Type 2 Diabetes: Caring burden and quality of life in caregivers - MirHosseini 1, Seyed Mohammad; Mohammadpourhodki 2, Reza; Abbasi 3, Ali; Basirinezhad 4, Mohammad Hasan; Ebrahimi 5*, Hossein (Shahroud Journal of Medical Sciences, 2020)
Background: Taking care of patients with chronic diseases such as diabetes exerts great tiredness and stress on the caregivers. The aim of this study was to determine the extent of the caring burden and its relationship with the quality of life of caregivers of diabetic patients. Methods: In this cross-sectional study, 154 caregivers of patients with type 2 diabetes referred to Imam Hossein hospital in Shahroud city were evaluated. The data collection tools included a demographic questionnaire, SF-36 standard quality of life questionnaire, and Novak & Guest care burden questionnaire. The accessible sampling was used and the data were collected by self-reporting. The data was analyzed using descriptive and inferential statistics (Pearson correlation coefficient and regression analysis). Significant level was set at 0.05. Results: The mean age of caregivers was 41.86 ± 12.78 years old. The mean scores of care burden and quality of life of the participants were 53.21 ± 49.61 and 61.02 ± 20.71 respectively. There was a significant inverse correlation between the mean score of care burden and caregivers’ quality of life. Conclusions: According to the results of this study, providing social and informational support for caregivers is recommended to reduce the care burden and subsequently improve the quality of life. Key words: Caring pressure, Quality of life, Diabetes, Caregiver.